Organizational principles of 3D genome architecture. Issue 12 (December 2018) - Rowley, M.; Corces, Victor
Abstract Studies of 3D chromatin organization have suggested that chromosomes are hierarchically organized into large compartments composed of smaller domains called topologically associating domains (TADs). Recent evidence suggests that compartments are smaller than previously thought and that the transcriptional or chromatin state is responsible for interactions leading to the formation of small compartmental domains in all organisms. In vertebrates, CTCF forms loop domains, probably via an extrusion process involving cohesin. CTCF loops cooperate with compartmental domains to establish the 3D organization of the genome. The continuous extrusion of the chromatin fibre by cohesin may also be responsible for the establishment of enhancer–promoter interactions and stochastic aspects of the transcription process. These observations suggest that the 3D organization of the genome is an emergent property of chromatin and its components, and thus may not be only a determinant but also a consequence of its function. High-resolution studies of chromosome conformation are revealing that the 3D genome is organized into smaller structural features than was previously supposed and is primarily composed of compartmental domains and CTCF loops. In this Perspectives article Rowley and Corces describe the latest views on the organizational drivers and principles of the 3D genome, and the interplay between genome activity and organization.